1946
DOI: 10.1002/qj.49707231105
|View full text |Cite
|
Sign up to set email alerts
|

Upper winds over the world: Part I. The frequency distribution of winds at a point in the free air

Abstract: BROOKS, I).SC., c'. 5 . L)lRST, B.A., and N. C.\KKCiTHIiRS, c . 5~ 1 . INTHOI~TCTION FCEE AIKFor the greater part of tho world, data of wind direction and velocity in the free air a r e very scanty or non-existent. In many countries pilot balloon observations have been taken for many years, but the wind roses obtained lrom these are inaccurate and misleading for two reasons: (a) because data are obtained only for days on which the balloon was not hidden by cloud ; and (b) because with increase of height fewer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1956
1956
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Carta et al (2008) and Han et al (2018) are amongst the few studies that assess wind speed and direction together as a vector using their joint distribution p(V,θ). Brooks et al (1946) were the first to suggest that the horizontal wind vector should be resolved into two orthogonal components which avoids issues with the circularity of θ. They assumed that each component was formed by the sum of random eddies and, hence, was Normally distributed.…”
Section: Introductionmentioning
confidence: 99%
“…Carta et al (2008) and Han et al (2018) are amongst the few studies that assess wind speed and direction together as a vector using their joint distribution p(V,θ). Brooks et al (1946) were the first to suggest that the horizontal wind vector should be resolved into two orthogonal components which avoids issues with the circularity of θ. They assumed that each component was formed by the sum of random eddies and, hence, was Normally distributed.…”
Section: Introductionmentioning
confidence: 99%
“…Brooks et al (1946) parameterised short-duration balloon sonde and surface observations, by resolving the horizontal wind vector into orthogonal x and y components acting around the mean vector, on the assumptions that both components were normally distributed and uncorrelated, with means,  x and  y , and equal standard deviations,  x =  y . In the Brooks model, contours of equal joint probability density function (jPDF) appear as concentric circles around the mean vector in the vector plane.…”
Section: Introductionmentioning
confidence: 99%
“…An early attempt to formulate a model for this parent was made by Brooks et al (, ). They suggested that the wind vector be resolved into orthogonal x and y components relative to a set of arbitrarily oriented Cartesian axes, each component Normally distributed and mutually independent.…”
Section: Implementation Of Mis and Lmands Methodsmentioning
confidence: 99%